Impact of spinach thylakoid extract-induced 12-week high-intensity functional training on specific adipokines in obese males - Ayoub Saeidi; Pezhman Motamedi; Maha Hoteit; Zahra Sadek; Wiam Ramadan; Marjan Mansouri Dara; Abdullah Almaqhawi; Shahnaz Shahrbanian; Hossein Abednatanzi; Kurt A Escobar; Zhaleh Pashaei; Maisa Hamed Al Kiyumi; et al. (Taylor & Francis Group, 2024)
Background Obesity presents multifarious etiopathologies with its management being a global challenge. This article presents the first ever report on the impact of spinach thylakoid extract-induced high-intensity functional training (HIFT) on obesity management via regulating the levels of novel adipokine, C1q/TNF-related Protein-12 (CTRP-12), furin, and Krüppel-like factor 15 (KLF-15).Methods Sixty-eight obese male subjects were randomly divided into four groups: control group (CG), supplement group (SG), training group (TG), and the combined training and supplement group (TSG). After initial assessments of all groups, the training group commenced a twelve-week HIFT using the CrossFit program (comprising of three training sessions per week, each lasting 30 min). Eligible candidates were randomly assigned to either receive thylakoid-rich spinach extract (5 g per day) or a matching placebo (5 g per day of corn starch, 30 min before lunch) for a total duration of 12 weeks. All required data and investigations were collected at 48 h pre- and post-training.Results The results indicated a substantial correlation between exercise and the time of KLF-15, furin, and CTRP-12 demonstrating effect sizes of 0.3, 0.7, and 0.6, respectively. Additionally, the training and supplementation group (TSG) exhibited a substantial decrease in low-density lipoprotein (LDL), total cholesterol (TC), and triglyceride (TG) levels (p < 0.0001). Concurrently, there was a significant increase in high-density lipoprotein-cholesterol (HDL-C) levels (p = 0.0001). Furthermore, a notable difference between the groups emerged in HDL, LDL, TC, and TG levels, supported by effect sizes of 0.73, 0.86, 0.96, and 0.89, respectively (p < 0.05).Conclusion The study offered novel insights into the management of obesity using supplements induced by spinach-derived thylakoid extract during a 12-week HIFT program. The proposed combination intervention may reverse obesity-induced insulin resistance and metabolic dysfunctions by positive regulation of CTRP-12/adipolin and KLF15 and simultaneous suppression of furin levels.